Reimagining Tithing in the Selected New Prophetic Churches in South Africa: a Social Scientific Approach - Kgatle, Mookgo Solomon (Scriptura, 2025)
The new prophetic churches in South Africa and elsewhere in the continent practice giving. There are many aspects to the concept of giving, such as tithing, seeding, offerings, and so forth. Members of the new prophetic churches are expected to give a tenth of their income as an obligation of their membership. In current practice, the clergy are the main beneficiaries of tithes in the selected new prophetic churches. This article reimagines the practice of tithing in these churches through social-scientific theory. The article argues that the proceeds of tithes should not only benefit the pastors but also the rest of the congregants, particularly those who are living in poverty and the marginalised. This is achieved by introducing the practice of tithing from a biblical and historical point of view. The article also outlines the practices of tithing in Pentecostalism and applies the same in new prophetic churches in South Africa. The aim of the article is to demonstrate that tithing has the potential to benefit society and deal with social ills such as poverty.